Development of a Website-Based Stock and Sales Management Information System to Optimize MSME Business Processes - Reni Haerani; Praditya Adi Nugroho; Penny Hendriyati; Roy Amrulloh Ritonga (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
Many Micro, Small, and Medium Enterprises (MSMEs) still manage inventory and sales records manually, resulting in recording errors, delayed reporting, and low operational efficiency. This research aims to develop a web-based Inventory and Sales Management Information System to improve MSME business processes. The system development method used is the waterfall method, including needs analysis, design, implementation, and testing. The system was developed using PHP with the Laravel framework and a MYSQL database. The system has functionality for product and stock data management, sales transaction recording, and automatic sales report generation. Inventory is updated in real time because every sales transaction or stock addition is reflected in the database. Sales reports are generated automatically from transaction data without manual recaps. Testing and implementation results show that integrating the inventory and sales modules can reduce recording errors, speed up reporting, improve operational efficiency, and provide accurate, up-to-date information to support MSME business decision-making.